Transplantation of viral‐positive hepatitis C‐positive kidneys into uninfected recipients offers an opportunity to increase organ access. Issue 4 (10th March 2020) - Graham, Jay A.; Torabi, Julia; Ajaimy, Maria; Akalin, Enver; Liriano, Luz E.; Azzi, Yorg; Pynadath, Cindy; Greenstein, Stuart M.; Goldstein, Doctor Y.; Fox, Amy S.; Weiss, Jeffery M.; Powell, Tia P.; et al.
Abstract: The advent of direct‐acting antivirals (DAAs) has provided the impetus to transplant kidneys from hepatitis C virus‐positive donors into uninfected recipients (D+/R−). Thirty D+/R− patients received DAA treatment. Sustained virologic response (SVR12) was defined as an undetectable viral load in 12 weeks after treatment. An age‐matched cohort of uninfected donor and recipient pairs (D−/R−) transplanted during same time period was used for comparison. The median day of viral detection was postoperative day (POD) 2. The detection of viremia in D+/R− patients was 100%. The initial median viral load was 531 copies/μL (range: 10‐1 × 10 8 copies/μL) with a median peak viral load of 3.4 × 10 5 copies/μL (range: 804‐1.0 × 10 8 copies/μL). DAAs were initiated on median POD 9 (range: 5‐41 days). All 30 patients had confirmed SVR12. During a median follow‐up of 10 months, patient and graft survival was 100%, and acute rejection was 6.6% with no major adverse events related to DAA treatment. Delayed graft function was significantly decreased in D+/R− patients as compared to the age‐matched cohort (27% vs 60%; P = .01). D+/R− transplantation offers patients an alternative strategy to increase access.